The Effect of Epoxy Paint Mixed with Ramie Fiber on Mild Steel Plate on Coating Thickness and Adhesion Strength - Kholis, Nur; Mukhammad, Alaya Fadllu Hadi; Respati, Sri Mulyo Bondan (Suara Teknik : Jurnal Ilmiah, 2024)
Steel plates are one of the dominant materials used in the industrial world and building construction infrastructure. The problem with using steel plate materials is corrosion. This research aims to analyze the effect of epoxy paint mixed with ramie fiber on the coating thickness and adhesion on mild steel plates. The main materials used in this research are mild steel plates and ramie fiber powder as a mixture in the epoxy paint. The steel plates were coated using epoxy paint mixed with ramie fiber powder in compositions of 100:1 gram, 100:2 grams, and 100:3 grams. Coating thickness testing was conducted using a digital coating paint meter, and adhesion testing was carried out using the cross cut and X cut methods according to ISO standards. The highest thickness value was found in the epoxy paint mixed with ramie fiber powder at a percentage of 3 grams, with an average value of 0.766 mm. In the adhesion test results, both the cross cut and X cut methods showed the best results with the ramie fiber powder mixture at percentages of 2 grams and 3 grams. These results are in accordance with ISO standards at a value of 0%, which means the cut edges are perfectly smooth; no grid squares are detached (excellent).